Prospek yang Sangat Menjanjikan Pasar Modal dan Investasi Berbasis Syariah - Dini Selasi; Lukmannul Hakim; Rifqi Faturahman (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Sharia Capital and Investment Market is part of the financial market based on Islamic sharia principles. The main goal is to ensure that investment and securities trading activities are in accordance with Islamic rules and values, such as fairness, transparency, and the prohibition of usury, gharar (uncertainty), and maysir (speculation). This system supports the development of sharia-based investment which continues to increase in line with the awareness of the Muslim community to manage their finances in accordance with sharia.